Squamous cell carcinoma arising in ovarian mature cystic teratoma: report of three cases - Bashyal, R; Lee, MC (Journal of Pathology of Nepal, 2012)
Malignant transformation of mature cystic teratoma of the ovary is rare. A wide variety of malignant tumors may arise within benign mature cystic teratoma. The most common form of malignant transformation of a mature cystic teratoma is squamous cell carcinoma. We report a series of three cases that developed squamous cell carcinoma in a benign ovarian cystic teratoma. Two of the carcinomas occurred in postmenopausal women: 51-year-old (case # 2) and 60 year-old (case # 3). The first case occurred in a 33-year-old woman. Histologically, all three cases were moderately differentiated squamous cell carcinomas and were confined to the ovaries. The aim of this study was to review our experience with this disease and to review the literature. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6032 JPN 2012; 2(3): 248-250